Trait-space disparity in fish communities spanning 380 million years from the Late Devonian to present - John Llewelyn; John A. Long; Richard Cloutier; Alice M. Clement; Giovanni Strona; Frédérik Saltré; Michael S.Y. Lee; Brian Choo; Kate Trinajstic; Olivia Vanhaesebroucke; Austin Fitzpatrick; Corey J.A. Bradshaw (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Behavioral evidence suggests facultative scavenging by a marine apex predator during a food pulse - Neil Hammerschlag; Ian Bell; Richard Fitzpatrick; Austin J. Gallagher; Lucy A. Hawkes; Mark G. Meekan; John D. Stevens; Michele Thums; Matthew J. Witt; Adam Barnett (Behavioral Ecology and Sociobiology, 2016)

C-reactive protein, interleukin-6, and prostate cancer risk in men aged 65 years and older - Brandon L. Pierce; Mary L. Biggs; Marvalyn DeCambre; Alexander P. Reiner; Christopher Li; Annette Fitzpatrick; Christopher S. Carlson; Janet L. Stanford; Melissa A. Austin (Cancer Causes & Control, 2009)

A gene family of putative immune recognition molecules in the hydroid Hydractinia - Ryan S. Schwarz; Linda Hodes-Villamar; Kelly A. Fitzpatrick; Matthew G. Fain; Austin L. Hughes; Luis F. Cadavid (Immunogenetics, 2007)